1998
DOI: 10.1038/nm0398-303
|View full text |Cite
|
Sign up to set email alerts
|

Infertility in female mice lacking the receptor for interleukin 11 is due to a defective uterine response to implantation

Abstract: During early pregnancy, in response to the implanting embryo, the surrounding uterine stroma undergoes a dramatic transformation into a specialized tissue known as the decidua. The decidua encapsulates the developing embryo, facilitating nutrient transfer and limiting trophoblast invasion. Here we show that female mice with a null mutation of the interleukin-11 receptor alpha chain are infertile because of defective decidualization. A temporal analysis revealed IL-11 expression is maximal in the normal pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
269
1
5

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 445 publications
(288 citation statements)
references
References 23 publications
12
269
1
5
Order By: Relevance
“…The gradient of RacGAP1 levels observed around the implantation site suggests that the embryoinduced modulation of hESC is highly localized and needs be spatially restricted during the invasion process. This phenomenon of localized modulation of genes by the embryo has been demonstrated in the stroma around implantation sites in the mouse for a number of different molecules, for example IL-11R␣ (42), but here it is demonstrated for human embryos.…”
Section: Discussionmentioning
confidence: 54%
“…The gradient of RacGAP1 levels observed around the implantation site suggests that the embryoinduced modulation of hESC is highly localized and needs be spatially restricted during the invasion process. This phenomenon of localized modulation of genes by the embryo has been demonstrated in the stroma around implantation sites in the mouse for a number of different molecules, for example IL-11R␣ (42), but here it is demonstrated for human embryos.…”
Section: Discussionmentioning
confidence: 54%
“…Surprisingly, mice with null mutations of GM-CSF or the bc chain (the signalling component of the GM-CSF receptor complex) had normal numbers of myeloid progenitors Nishinakamura et al, 1995;Robb et al, 1995). Analysis of mice in which either TPO or c-MPL was deleted revealed that, in addition to its activity as a Mid to late fetal lethality, multiple defects, including cardiac (ventricular) hypoplasia, abnormal placentation, reduced fetal liver hematopoiesis and reduced primordial germ cell number conditional deletion: female infertility and neurological, cardiac, hematopoietic, immunological, hepatic and lung defects, Yoshida et al (1996a) and Betz et al (1998) IL-6Ra IL-6 NA IL-11Ra IL-11 Viable, female infertility Nandurkar et al (1997) and Robb et al (1998) Ozaki et al (2002) and Frohlich et al (2007) Abbreviations: CNTF, ciliary neurotrophic factor receptor; CLCF, cardiotrophin-like cytokine factor; EPOR, erythropoietin receptor; GM-CSFR, granulocyte macrophage colony-stimulating factor receptor; IL, interleukin; LIFR, leukemia inhibitory factor receptor; NA, not available; NK, natural killer; OSM, oncostatin M; TPO, thrombopoietin.…”
Section: Knockouts Of Cytokine Receptorsmentioning
confidence: 99%
“…Disruption of the IL-7Ra led to early death due to severe lymphocyte hypoplasia, with deficiencies of B cells, T cells and natural killer cells, but the development of the earliest unipotent T-and B-cell precursors was found to be normal (Peschon et al, 1994;Maki et al, 1996). Gene targeting studies also revealed novel functions for cytokines, such as a role for GM-CSF and its receptor signalling in pulmonary physiology through regulation of alveolar macrophages and for IL-11Ra signalling in induction of the uterine response to embryo implantation (Nishinakamura et al, 1995;Robb et al, 1995;Robb et al, 1998). Mice with deletion of two or more cytokine receptors and/or cytokines have also been generated.…”
Section: Knockouts Of Cytokine Receptorsmentioning
confidence: 99%
“…IL-1 1 also has pleiotropic effects outside the hematopoietic compartment. Our receptor targeting strategy has also served to identify an additional role for IL-11 as a critically important mediator in reproductive physiology, since the IL-11Ra-/-female mice are infertile [22,97]. Another potentially important role for…”
Section: Resultsmentioning
confidence: 99%